2018
DOI: 10.1186/s13019-018-0792-8
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous versus thoracoscopic ablation of symptomatic paroxysmal atrial fibrillation: a randomised controlled trial - the FAST II study

Abstract: BackgroundThe most efficient first-time invasive treatment, for achieving sinus rhythm, in symptomatic paroxysmal atrial fibrillation has not been established. We aimed to compare percutaneous catheter and video-assisted thoracoscopic pulmonary vein radiofrequency ablation in patients referred for first-time invasive treatment due to symptomatic paroxysmal atrial fibrillation. The primary outcome of interest was the prevalence of atrial fibrillation with and without anti-arrhythmic drugs at 12 months.MethodsNi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
0
19
0
3
Order By: Relevance
“…Second, TA also had higher rates of adverse events particularly thoracic complications. The key clinical characteristics of eligible randomized trials include middle‐aged patients with a high prevalence of paroxysmal AF in 85%, AF duration of 5.9 years, high antiarrhythmic use in 95%, prior failed CA in approximately half, and normal mean left ventricular ejection fraction, but mildly dilated left atrial dimensions on echocardiography 7–12 . Therefore, patients with paroxysmal AF refractory to antiarrhythmic drugs and previous failed CA, but with preserved left ventricular function, are those that our findings best apply to.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Second, TA also had higher rates of adverse events particularly thoracic complications. The key clinical characteristics of eligible randomized trials include middle‐aged patients with a high prevalence of paroxysmal AF in 85%, AF duration of 5.9 years, high antiarrhythmic use in 95%, prior failed CA in approximately half, and normal mean left ventricular ejection fraction, but mildly dilated left atrial dimensions on echocardiography 7–12 . Therefore, patients with paroxysmal AF refractory to antiarrhythmic drugs and previous failed CA, but with preserved left ventricular function, are those that our findings best apply to.…”
Section: Discussionmentioning
confidence: 79%
“…Furthermore, the lower rate of repeat ablation during follow‐up (25% vs 2%) is another distinct advantage of TA. However, the high adverse event rates in up to 25% of TA even in randomized trials is important, observed across four of five studies reporting this 7,8,10,11 . In particularly, thoracic complications much higher in TA are detrimental because of their frequent need of invasive procedures, prolonging of intensive care and/or hospital stay, and potential for long‐term sequelae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies included both refractory paroxysmal and PeAF 6–8 . Two studies included only refractory paroxysmal AF 9,10 . One study included only PeAF 11 .…”
Section: Resultsmentioning
confidence: 99%
“…9 ). Some data suggest SA may be superior to CA for first-line treatment in PAF, however, at the cost of a higher rate of complications and longer hospitalization 4,6,8,10,11 . In contrast, in the review of Yi et al SA did not show better efficacy results as the first invasive procedure in the subgroup of patients with paroxysmal AF or early persistent AF (ref.…”
Section: Discussionmentioning
confidence: 99%